Robot manipulator dynamics - Towards better computational algorithms - Tenreiro Machado, J. A. (1988)
A new robot manipulator inverse dynamics computational algorithm is announced. The novel feature resides in the computations which are a blend of ordinary and Boolean algebra. As such, this method may also be interpreted as a dedicated compiler that optimizes the on-line computing time at expenses of the off-line stage. Nervertheless, the high off-line requirements are alleviated, through the derivation of some general rules that stem from the structure of the robot manipulator equations. In a practical implementation, a copmuter program based on a Quine-McCluskey truth table simplification method was used and experimented on a 2R robot manipulator. The results show a considerable computational improvement on a conventional sequential machine. Furthermore. they clearly point out new comptutational parallel architectures, without scheduling problems, and where performance improvement is porportional to the number of processors. Finally, it is observed that the proposed algorithm is not restricted to robot inverse dynamic computations, but also applicable to kinematic and control computations.